# 3. Order of Operations

**Problem:** There are 2 ways to answer this question involving numbers:

`2 + 3 xx 7`

We can either

**Add**the 2 and 3 first and then**multiply**the result by 7 (we would get 35), OR- We could
**multiply**the 3 and 7 then**add**the 2 (giving us 23).

Which is correct?

To reduce confusion and so that we all get the same answer when combining numbers using the operations of adding, subtracting, multiplying or dividing, the following convention is used.

### BODMAS

BODMAS is the agreed convention for answering problems that are a mixture of adding, subtracting, multiplying and dividing. It stands for:

B:Do what is inside bracketsfirstO:Order is important in mathematics!DM:Do divisionsandmultiplicationsas you come to them, fromleft to rightAS:Finally, do additionsandsubtractionsas you come to them, fromleft to right.

So for our problem above, the correct answer would be:

`2 + 3 xx 7`

`= 2 + 21`

`= 23`

### Example 1

Evaluate 10 − 2 × 3

Answer

10 − 2 × 3

= 10 − 6

= 4

### Example 2

Evaluate (10 − 2) × 3

Answer

This time we have the same numbers as the previous example, but the brackets tell us to do it differently:

(10 − 2) × 3

= 8 × 3

= 24

Always be careful with brackets. As you can see, they make a big difference.

### Example 3

Simplify −4 + 5 × (7 + 3)

Answer

We do the operations in **brackets** first:

(7 + 3) = 10

So the original problem is now

−4 + 5 × 10

We do the **multiplication** next (before even looking at the addition):

5 × 10 = 50

So the original problem now has become:

−4 + 50

And this equals

46

So −4 + 5 × (7 + 3) = 46

### Example 4

Simplify 12(5 + 6 × 3) ÷ (4 + 2)

Answer

The first bracket:

(5 + 6 × 3) = 5 + 18 = 23

The second bracket:

(4 + 2) = 6

So we have, since we need to work from left to right:

12 × 23 ÷ 6 = 46

So

12(5 + 6 × 3) ÷ (4 + 2) = 46

### Example 5

Simplify −2(*x* + 5 × 7 + 3)

[Note the difference between the letter "*x*" and the multiplication operator "×".]

Answer

Here, we consider the bracket first:

(

x+ 5 × 7 + 3)

We do the multiplication inside the brackets:

5 × 7 = 35

So the whole bracket will be:

x+ 35 + 3 =x+ 38

Now for the -2 out the front:

−2(

x+ 38)= −2

x−76